A Newly Identified Mint Control Link in the Coinage of Andragoras and Sophytes - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2022)
An extensive array of the of the once rare silver coinage of Andragoras and Sophytes has appeared recently in numismatic trade. This has more than tripled the corpus of known specimens compared to that documented in the typology of the coinage struck by these two rulers in Parthia in the period c. 250s-238 BC. For the most part, new types identified among the coins in commerce served to extend previously identified suites of mint controls to different denominations in each series, or more rarely and significantly to other series in the coinage. A notable example of the latter is a newly identified anepigraphic Andragoras Series 4 (laureate head of Zeus r./eagle standing l., head reverted) diobol on the reverse of which is found the kerykeion symbol above a grape vine branch . Previously, the latter was the only known symbol on Series 4. The addition of the kerykeion symbol to the repertoire of Series 4 mint controls characterizes this new type as an example of the previously unknown Series 4.3.